2020
DOI: 10.3390/jcm9072196
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Saliva in Diabetic Xerostomia (ASDIX): Double Blind Trial of Aldiamed® Versus Placebo

Abstract: Xerostomia is a symptom frequently present in patients with type 1 (T1DM) and type 2 diabetes mellitus (T2DM). In the present trial, the activity of an artificial saliva (aldiamed® spray) in comparison to a placebo spray were used to evaluate the xerostomia and the saliva antioxidant capacity (SAT). Sixty patients of both genders with T1DM or T2DM were randomized into two groups of 30 subjects each. The experiment was a double-blind study approved by the Ethics Committee of the “G. d’Annunzio University” of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In fact, it has been shown that xerostomia can also be induced by different drug therapies such as: antidepressants, antipsychotics, anticholinergics, antihypertensives, antihistamines, and sedatives [ 33 ]. Furthermore, there is strong evidence that xerostomia is very common in diabetic patients and may be present in >50% of cases, and recently it was reported that the use of artificial saliva spray was shown to be effective in the treatment of xerostomia in type 1 and type 2 diabetes [ 34 , 35 ]. However, in our study, only 15% of patients were affected by diabetes (not specified if type 1 or type 2).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that xerostomia can also be induced by different drug therapies such as: antidepressants, antipsychotics, anticholinergics, antihypertensives, antihistamines, and sedatives [ 33 ]. Furthermore, there is strong evidence that xerostomia is very common in diabetic patients and may be present in >50% of cases, and recently it was reported that the use of artificial saliva spray was shown to be effective in the treatment of xerostomia in type 1 and type 2 diabetes [ 34 , 35 ]. However, in our study, only 15% of patients were affected by diabetes (not specified if type 1 or type 2).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials involving cisplatin, melatonin, and/or levocarnitine still hold the promise for better outcomes in the prevention and treatment of xerostomia. In addition, for disease conditions such as diabetes mellitus causing salivary gland dysfunction which results in salivary flow reduction and a change in saliva composition, significant mitigation of subjective xerostomia may be achieved through artificial saliva [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this high prevalence, studies that examined treatment options specific for diabetes‐induced xerostomia were found to be relatively scarce. In fact, up to the authors' knowledge, only one clinical trial was performed in 2020 by Sinjari et al (2020), in which the activity of an artificial saliva spray (Aldiamed® spray) was tested in comparison to a placebo spray for the management of xerostomia in patients with DM.…”
Section: Discussionmentioning
confidence: 99%